If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y(4)=0
We simplify the equation to the form, which is simple to understand
2y(4)=0
Reorder the terms in parentheses
+(+8y)=0
Remove unnecessary parentheses
+8y=0
We move all terms containing y to the left and all other terms to the right.
+8y=0
We simplify left and right side of the equation.
+8y=0
We divide both sides of the equation by 8 to get y.
y=0
| -8x+2= | | -10q+5y+6-2q-y-6= | | -3(b+7)=6(b+4) | | 0=3x^2-6x+5 | | =(n+2)(2n+5) | | 2-82x=122 | | 2x+ine^4x=12 | | 17x+5=19x-7 | | 2x+10=2x-20 | | y=12+6x | | 6(5a+7)-7(-6-6a)=-60 | | 15-3b=12-2b | | 82-122x=2 | | 9x-7w+4x+6y+2y+3w= | | 8x-9=10-9x+12-x | | 39-(x+9)=7x-2 | | 4x^2+12x+81=0 | | 2x^2+2x=15 | | 3a=15-2a | | y=-4+x | | 7y-5-y-3= | | 122-82x=2 | | -8(4+6p)+8(1-6p)=72 | | -8x-9=10-9x+12-x | | 6x-30=34-2x | | 5+49x=21x+37 | | -0.5=-0.25(c+7) | | 4x+7=56 | | 0=27+v-4(3+v) | | -4x-4y=-3 | | [x]=3.4 | | 7y-5fromy-3= |